2019
DOI: 10.3390/microorganisms7110485
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Initial Growth Process and the Infection Mechanism of Penicillium digitatum on Postharvest Citrus (Citrus reticulata Blanco)

Abstract: Green mold disease, a common citrus post-harvest disease caused by Penicillium digitatum, has an unresolved initial infection mechanism. Understanding the infection mechanism leads to the development of potential controls and preventive measures against the disease. The present study aimed to delineate the infection mechanism by investigating spore germination, changes of organic molecules and enzyme activity, and differential expression of genes in the P. digitatum infection. P. digitatum spore germination wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…CWDEs are the most frequently reported pathogenic factors of plant pathogens. The large number of genes, associated with the synthesis of CWDEs, found in this study were already reported in our previous study [12]. In addition, the pH of the host environment is closely related to the synthesis and activity of CWDEs.…”
Section: Analysis Of Key Degs Of P Digitatum In Infection Processsupporting
confidence: 85%
See 3 more Smart Citations
“…CWDEs are the most frequently reported pathogenic factors of plant pathogens. The large number of genes, associated with the synthesis of CWDEs, found in this study were already reported in our previous study [12]. In addition, the pH of the host environment is closely related to the synthesis and activity of CWDEs.…”
Section: Analysis Of Key Degs Of P Digitatum In Infection Processsupporting
confidence: 85%
“…However, transcriptome analysis hasn't been used to determine the infection mechanism of P. digitatum in citrus fruits and thus the molecular mechanism behind the infection process is lacking. Therefore, this study sampled the P. digitatum infection in citrus at key time points as revealed in our previous study [12], and explored the key genes and pathways through high-throughput transcriptome sequencing, that reveal its infection mechanism at the molecular level. P. digitatum spores can activate rapidly and start colonization after they come into contact with citrus wounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these pathogens, P. digitatum, the causal agent of green mold, is considered one of the most threatening postharvest diseases in citrus fruit. The P. digitatum infection on citrus fruit has posed a series of adverse effects including toxins accumulation, postharvest deterioration, human health, environmental pollution, and 60-80% of postharvest crop loss in China [7,8]. To reduce the incidence of green mold, a variety of synthetic fungicides have been commonly used to ensure a stable supply of citrus fruit at markets for a growing world population [9,10].…”
Section: Introductionmentioning
confidence: 99%